DETERMINATION AND CATEGORIZATION OF THE VARIATIONS IN THE PALATAL RUGAE BETWEEN INDIAN AND NEGROID POPULATION - Bhardwaj, Ishika; Lukose, Sally; Siddharth, M (Journal of Forensic Medicine and Toxicology, 2025)
Palatal rugoscopy is the examination of the palatal rugae. Most people agree that a person’s rugae pattern doesn’t vary over their lifespan. The rugae pattern can endure injury or burns better than most other anatomical structures because of their interior placement in the head. Rugae patterns are also used for personal identification because they are thought to be distinctive like fingerprints. The purpose of this study was to identify and compare the palatal rugae of North Indians and Negroids in terms of quantity, size, and morphology. The study consists of two groups between North Indians and Negroids. 40 plaster casts, aged between 18 and 25, evenly distributed between two groups and genders make up the sample. Alginate impression material was used to create a plaster cast after obtaining an impression of the maxillary arch. Using a sharp graphite pencil and sufficient lighting and magnification, the rugae were identified on the cast and classified in accordance with Thomas and Kotze (1983) and Kapali et al. (1983). Total rugae count was lesser in Indian subjects as compared to the Negroid subjects. The mean rugae count on the left side of the Indian subjects (5.90 ± 1.48) was significantly lesser (p=0.016) than Negroid subjects (7.30 ± 2.00). Rugae size did not differ among Indian and Negroid subjects. The shapes of the rugae varied greatly between the two groups (p=0.003) with the most prominent rugae shape in the Indian population being the curved shape (49.20%) and the most prominent rugae shape in the Negroid population being the straight shape (37%). Given the limits of the current study, it is possible to draw the conclusion that another technique of identifying North Indian and Negroid is the rugae pattern.